Case Report: The third-generation sequencing confirmed a novel 7.2 Kb deletion at β-globin gene in a patient with rare β-thalassemia - Zhong, Guoxing; Zhong, Zeyan; Guan, Zhiyang; Chen, Dina; Wu, Zhiyong; Yang, Kunxiang; Chen, Dan; Liu, Yinyin; Xu, Ruofan; Chen, Jianhong (Frontiers in Genetics, 2022)
Background: Thalassemia was the most common monogenic diseases worldwide, which was caused by mutations, deletions or duplications in human globin genes which disturbed the synthesis balance between α- and β-globin chains of hemoglobin. There were many classics methods to diagnose thalassemia, but all of them had limitations. Although variations in the human β-globin gene cluster were mainly point mutations, novel large deletions had been described in recent years along with the development of DNA sequencing technology. Case report: We present a case of 32-year-old male with abnormal hematological results. However, 23 genotypes of the most common thalassemia were not detected by two independent conventional platforms. Finally, using multiplex ligation-dependent probe amplification (MLPA), third-generation sequencing (TGS) and Gap PCR detection methods, we first confirmed the case with a novel 7.2 Kb deletion (Chr11:5222800-5230034, hg38) located at HBB gene. Conclusions: Our results showed that TGS technology was a powerful tool for thalassemia breakpoint detection, had promising potentiality in genetic screening of novel thalassemia, especially for the novel deletions in globin genes.